Struktur Naratif Iklan Kebaikan Melampaui Batasan pada YouTube Pertamina - Lubis, Chalisa Audia; Nasution, Nurhasanah (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
Advertisements not only function as a means of promoting products or services, but also as a medium to increase public awareness of social and environmental issues. The advertisement of the movement of kindness beyond limits is an advertisement that emphasizes moral and social education. This study aims to analyze how the stages of narrative structure in the advertisement of the movement of kindness beyond limits form the delivery of moral messages. This study uses a qualitative descriptive research method with a structuralist narrative analysis approach by Tzvetan Todorov and the moral theory of Burhan Nurgiyantoro. The data collection technique in this study uses observation and documentation techniques with data analysis techniques using the Miles and Huberman model, namely data reduction, data presentation, and verification of conclusions. Data were analyzed through the identification of Todorov's narrative stages (equilibrium, disruption, recognition, repair the damage, new equilibrium) and Nurgiyantoro's moral perspective. The results of the study show that the narrative stages in advertisements are interrelated in forming moral messages. Advertisements progressively lead the audience to understand the context, feel empathy for the characters, and accept the moral messages conveyed. The main message in this advertisement emphasizes the importance of empathy, social concern, and solidarity in community life